7T MR spectroscopic imaging in the localization of surgical epilepsy. Issue 9 (29th July 2013) - Pan, Jullie W.; Duckrow, Robert B.; Gerrard, Jason; Ong, Caroline; Hirsch, Lawrence J.; Resor, Stanley R.; Zhang, Yan; Petroff, Ognen; Spencer, Susan; Hetherington, Hoby P.; Spencer, Dennis D.
Summary Purpose With the success that surgical approaches can provide for localization‐related epilepsy, accurate seizure localization remains important. Although magnetic resonance (MR) spectroscopy has had success in earlier studies in medial temporal lobe epilepsy, there have been fewer studies evaluating its use in a broader range of localization‐related epilepsy. With improvements in signal‐to‐noise with ultra‐high field MR, we report on the use of high resolution 7T MR spectroscopic imaging (MRSI) in 25 surgically treated patients studied over a 3.5‐year period. Methods Patients were included in this analysis if the region of MRSI study included the surgical resection region. Concordance between region of MRSI abnormalities and of surgical resection was classified into three groups (complete, partial, or no agreement) and outcome was dichotomized by International League Against Epilepsy (ILAE) I–III and IV–VI groups. MRSI was performed with repetition time/echo time 1.5 s/40 msec in two‐dimensional (2D) or three‐dimensional (3D) encoding for robust detection of singlets N‐acetyl aspartate (NAA), creatine (Cr), and choline with abnormalities in NAA/Cr determined with correction for tissue content of gray matter. Key Findings The concordance between MRSI‐determined abnormality and surgical resection region was significantly related to outcome: Outcome was better if the resected tissue was metabolically abnormal. All 14 patients with complete resection of the region with the most severe metabolic abnormality had good outcome, including five requiring intracranial electroencephalography (EEG) analysis, whereas only 3/11 without complete resection of the most severe metabolic abnormality had good outcome (p < 0.001). Significance This is consistent with the seizure‐onset zone being characterized by metabolic dysfunction and suggests that high resolution MRSI can help define these regions for the purposes of outcome prediction.